2009
DOI: 10.24266/0738-2898-27.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Mulch Depth Affects Weed Germination

Abstract: With environmental concerns increasing, non-chemical weed control in container plant production is increasing in the United States. Pine bark mini-nuggets were evaluated as a non-chemical weed control technique for two weed species; Chamaesyce maculata (L.) Small (spotted spurge) and Eclipta alba (L.) Hassk.(eclipta). On June 19, 2006, seed (25 per container) were directly placed on the potting substrate surface of #3 containers before mulching with pine bark mini-nuggets to a depth of either 0, 1.27 or 2.54 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…Depths of at least 2.5 cm were required for PB and PS to achieve at least 60% reduction in emergence of garden spurge and crabgrass in outdoor and greenhouse experiments. This result is similar to previous findings with flexuous bittercress, yellow woodsorrel (Oxalis stricta L.) (Richardson et al 2008), and spotted spurge (Cochran et al 2009), in which PB depths of at least 2.5 cm were needed to reduce germination of top-positioned seed. At PB depths of ≤1.3 cm, data reported by Cochran et al (2009) and Richardson et al (2008) are in agreement with data reported here, suggesting that many weed species will be able to germinate and could possibly root into soil beneath such a shallow mulch depth.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…Depths of at least 2.5 cm were required for PB and PS to achieve at least 60% reduction in emergence of garden spurge and crabgrass in outdoor and greenhouse experiments. This result is similar to previous findings with flexuous bittercress, yellow woodsorrel (Oxalis stricta L.) (Richardson et al 2008), and spotted spurge (Cochran et al 2009), in which PB depths of at least 2.5 cm were needed to reduce germination of top-positioned seed. At PB depths of ≤1.3 cm, data reported by Cochran et al (2009) and Richardson et al (2008) are in agreement with data reported here, suggesting that many weed species will be able to germinate and could possibly root into soil beneath such a shallow mulch depth.…”
supporting
confidence: 91%
“…This result is similar to previous findings with flexuous bittercress, yellow woodsorrel (Oxalis stricta L.) (Richardson et al 2008), and spotted spurge (Cochran et al 2009), in which PB depths of at least 2.5 cm were needed to reduce germination of top-positioned seed. At PB depths of ≤1.3 cm, data reported by Cochran et al (2009) and Richardson et al (2008) are in agreement with data reported here, suggesting that many weed species will be able to germinate and could possibly root into soil beneath such a shallow mulch depth. Shallow mulch depths (≤1.3 cm) may also allow seeds to be washed beneath mulch layers where they may germinate and emerge from the soil beneath the mulch, as the physical barrier would be minimal.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Due to the cost of hand weeding and challenges associated with PRE herbicides, growers and researchers have investigated use of various nonchemical tools for weed control, including organic mulch such as pine bark (Cochran et al 2009;Richardson et al 2008;Wilen et al 1999), rice hulls (Case et al 2005), and weed disks or similar products that are secured on the container medium surface (Amoroso et al 2009;Chong 2003;Mathers 2003). All of these methods have been found to be as or more effective than a single herbicide application, but cost and availability often prohibit widescale adoption (Stewart et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving plant growth (Greenly and Rakow, 1995), organic mulches have been shown to reduce weed seed germination (Cochran et al, 2009;Richardson et al, 2008) through light exclusion, reduction of available water for weed seeds, allelopathy, and by acting as a barrier to emerging seedlings (Chalker-Scott, 2007). The exact method in which mulches reduce weed growth is not known for all mulch types, but light exclusion has been attributed as being the most common method (Teasdale and Mohler, 2000) as most weed seeds require light to germinate (Wesson and Wareing, 1967).…”
mentioning
confidence: 99%